Design of a library of generic accelerators of DNN-based inference algorithms for low-end FPGAs - León-Vega, Luis Gerardo (2022)
Proyecto de Graduación (Maestría en Electrónica) Instituto Tecnológico de Costa Rica, Escuela de Ingeniería Electrónica, 2022.